The Legacy of Democratic Burden - Raharjo, Agus (Jurnal Dinamika Hukum, 2019)
Simultaneous general elections held on April 17th 2019 will enter a new phase, it is anopen campaign. The actual excesses that have occurred long before the open campaign began.Attacking each other between candidates - both presidential and deputy candidates, as well asprospective legislative members has revealed its action through electronic media. Campaignersfrom each party have also issued movement to defend their hero and program, as well aspersonal vices and their image.